Penerapan Analisis Data Panel Pada Suhu Udara Terhadap Perubahan Iklim Curah Hujan di Kota Padang - Muthahharah, Isma; Hafid, Hardianti (Program Studi Matematika Universitas Sulawesi Barat, 2024)
Climate is the average weather conditions that prevail over an extended period in a particular region. The complex climate system, comprising components such as the atmosphere, lithosphere, and biosphere, generates climate variations among different areas. Climate change has potential impacts such as changes in rainfall patterns, rising temperatures, and sea level rise. Extreme weather, prolonged droughts, and heatwaves can endanger both the environment and human beings.This article aims to assist in predicting future climate patterns to prepare for their impacts using panel data analysis. A panel data regression model is employed to assess the influence of rainfall and air temperature on climate change in Kota Padang from 2018 to 2022. The analysis reveals a significant influence of air temperature, estimated at 0.08, on climate change in Kota Padang during this period. These findings provide a basis for developing mitigation and adaptation strategies to address climate challenges in the region and offer valuable insights for government policies in facing future climate-related issues.